Community-based participatory research through virtual communities - Tamí-Maury, Irene (J Commun Healthc, 2017)
BACKGROUND: Over the last quarter century many new cyberspace platforms have emerged that facilitate communication across time, geographical distance and now even language. Whereas brick-and-mortar communities are defined by geographically local characteristics, a virtual community is an online community of individuals who socialize and connect around a common interest or theme using the Internet. Community-based participatory research (CBPR) is a public health approach that requires equitable partnerships between community members and researchers. Virtual communities abound on the Internet today, yet their application to CBPR is rarely considered. METHODS: We examine three case studies to explore the advantages and challenges of virtual communities for CBPR, as well as several of the online tools CBPR practitioners can use to facilitate virtual community participation. RESULTS: There is a potential utility of virtual communities in supporting CBPR efforts as they reduce the effects of geographical barriers, maximize the growth potential of the community, and provide portable and affordable channels forreal-time communication. Some caveats indicated in our case studies are: technological challenges, difficulty in crediting members’ contributions and determining ownership of content, no face-to-face interaction may hinder relationship formation, cohesion, and trust resulting in lower engagement. CONCLUSIONS: The paper concludes with recommendations for the use of virtual communities in CBPR projects, such as in the coordination of statewide health care policy initiatives and in the dissemination of best public health practices.